Artworks as dichotomous objects: implications for the scientific study of aesthetic experience - Pepperell, Robert (Frontiers in Human Neuroscience, 2015)
This paper addresses an issue that has been studied from both scientific and art theoretical perspectives, namely the dichotomous nature of representational artworks. Representational artworks are dichotomous in that they present us with two distinct aspects at once. In one aspect we are aware of what is represented while in the other we are aware of the material from which the representation is composed. The dichotomy arises due the incompatibility, indeed contradiction, between these aspects of awareness, both of which must be present if we are to fully appreciate the artwork. Examples from art history are given to show how artists have exploited this dichotomy in a way that conditions our response to their work. I hypothesize that the degree of manifest dichotomy in a work determines the strength of its aesthetic effect, and propose this could be experimentally tested. I conclude that scientific studies of aesthetic experience should take the dichotomous nature of artworks into account.